The effect of dry headspace on the thermal resistance of bacteria in peanut oil and peanut butter in thermal treatments. (July 2022) - Yang, Ren; Cheng, Teng; Hong, Yoonki; Wei, Lina; Tang, Juming
Abstract: The objective of this study was to investigate the effect of a dry headspace on the thermal resistance of bacteria in lipid oil and peanut butter. Our recent study found Enterococcus faecium to be extremely resistant to heat in a thin oil layer when exposing to a dry environment. Thus, we hypothesized that peanut oil or peanut butter that is in contact with dry air during a thermal process may cause surface drying and, therefore, protect bacteria from heat inactivation. In this research, we treated peanut oil (aw = 0.31 at 80 °C) and peanut butter (aw = 0.38 at 80 °C) inoculated with Salmonella Enteritidis PT30 ( S. Enteritidis) or Enterococcus faecium NRRL B-2354 ( E. faecium ) at 80 °C using two types of hermetically sealed sample holders, one with negligible headspace and the other with a large headspace. The results indicated that S. Enteritidis and E. faecium in peanut oil and peanut butter became significantly ( P < 0.05) more resistant to heat when treated in sample holders with large headspace compared to in fully filled sample holders with negligible headspace. When the sample holder head space was switched from "Negligible" to "Large", the thermal death time ( D 80 -value) of E. faecium increased 16.7 times in oil and 4.3 times in peanut butter; the D 80 -value of S . Enteritidis increased 4.6 times in peanut oil and 2.6 times in peanut butter. When plotted vs. the material water activity measured at the treatment temperature (80 °C), the D 80 -value of both bacteria agreed well with reported data obtained from other low-moisture foods, indicating that the local water activity of the sample was the dominating factor and surface drying was the cause to the enhanced thermal resistance. This study illustrates the importance of selecting appropriate test cells in isothermal studies on thermal resistence of bacteria in high fat low moisture foods. It also suggests that food industry should be cautious about surface drying in the pasteurization of low-moisture products. Highlights: Headspace in sample holders enhances the D- value of bacteria in peanut butter and oil. Surface drying was the cause of the enhanced thermal resistance. Thermal death of Salmonella and Enterococcus in peanut butter followed the first-order kinetics. The dry spot in a product may be a control point of a thermal pasteurization process.